2007
DOI: 10.1142/s0219876207001308
|View full text |Cite
|
Sign up to set email alerts
|

The Upper Bound Property for Solid Mechanics of the Linearly Conforming Radial Point Interpolation Method (Lc-Rpim)

Abstract: It has been proven by the authors that both the upper and lower bounds in energy norm of the exact solution to elasticity problems can now be obtained by using the fully compatible finite element method (FEM) and linearly conforming point interpolation method (LC-PIM). This paper examines the upper bound property of the linearly conforming radial point interpolation method (LC-RPIM), where the Radial Basis Functions (RBFs) are used to construct shape functions and node-based smoothed strains are used to formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 12 publications
3
46
0
Order By: Relevance
“…In such cases, we can still expect Equation (83) holds approximately and hence a convergence rate of 1.5 in G 1 semi-norm. This has been confirmed in many numerical examples presented in [22,26,33], where numerical rates of about 1.4 were often found. We were excited about the higher convergence rate, but could not give a good explanation then.…”
Section: Comparison With H 1 Norm Measuressupporting
confidence: 62%
See 1 more Smart Citation
“…In such cases, we can still expect Equation (83) holds approximately and hence a convergence rate of 1.5 in G 1 semi-norm. This has been confirmed in many numerical examples presented in [22,26,33], where numerical rates of about 1.4 were often found. We were excited about the higher convergence rate, but could not give a good explanation then.…”
Section: Comparison With H 1 Norm Measuressupporting
confidence: 62%
“…To produce a softer model, Liu discovered that we can simply create a model that uses a smaller number (but larger than the minimum number) of smoothing domains, as it is done in the NS-PIM [19,26] and in NS-RPIM [33]. Theoretically, one can make a model as softer as desired and can even make a model that is singular!…”
Section: A Discussion On Soft and Stiff Modes: Upper And Lower Boundsmentioning
confidence: 99%
“…However, the energy obtained from NS-PIM is an overestimate of the exact energy, and the displacement is always an upper bound of the exact solution in the energy form [17]. For the gravity dam, we also prove the energy bound property as shown in Figure 12.…”
Section: Strain Energy and Displacementmentioning
confidence: 62%
“…It was found that NS-PIM is at least linearly conforming, can provide much better stress solutions, is much more tolerant to mesh distortion, is immune from volumetric locking and works well for linear triangular and tetrahedral background cells [16]. More important, the NS-PIM can obtain an upper bound solution in energy norm for elasticity problems with homogeneous essential boundary conditions [16,17]. Owing to the excellent properties, the NS-PIM (and NS-RPIM [18]) has been further developed for conducing the adaptive analysis [19], the contact problems [20], the heat transfer and the thermoelasticity problems [21,22] and provides upper bound solutions in energy norm as it does for elasticity problems.…”
Section: Introductionmentioning
confidence: 99%
“…Combining the system in Equation (26) and the system in Equation (13) with a continuous scalar scaling factor ∈[0, 1] leads to the following potential energy functional of -FEM for 2-D problems:ˆ From Equation (27), one can note that…”
Section: Potential Energy Functional Of -Femmentioning
confidence: 99%